2020
DOI: 10.3389/fmicb.2020.01524
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Wildlife in Guadeloupe (French West Indies): Distribution of a Single blaCTX–M–1/IncI1/ST3 Plasmid Among Humans and Wild Animals

Abstract: Limited data are available on the contribution of wildlife to the spread of antibacterial resistance. We determined the prevalence of resistance to antibiotics in Escherichia coli isolates collected from wild animals in 2013 and 2014 and the genetic basis for resistance to third-generation cephalosporin in Guadeloupe. We recovered 52 antibioticresistant (AR) E. coli strains from 48 of the 884 (5.4%) wild animals tested (46 iguanas, 181 birds, 289 anoles, and 368 rodents at 163 sampling sites). Rodents had high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Previous work on ESBL-producing strains in wildlife in Guadeloupe was less worrisome. Results were focused on E. coli carriage and showed that only 7/884 animals (0.79%) were positive, comprising 5 rats ( Rattus norvegicus ), 1 Carib grackle ( Quiscalus lugubris ), and 1 iguana ( Iguana iguana ) ( 22 ). The difference from our results may be due to lower exposure to anthropogenic pollution in the previous work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work on ESBL-producing strains in wildlife in Guadeloupe was less worrisome. Results were focused on E. coli carriage and showed that only 7/884 animals (0.79%) were positive, comprising 5 rats ( Rattus norvegicus ), 1 Carib grackle ( Quiscalus lugubris ), and 1 iguana ( Iguana iguana ) ( 22 ). The difference from our results may be due to lower exposure to anthropogenic pollution in the previous work.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of great concern because of the many ST114 clones isolated in clinical samples and because of the capacity of ST114 to spread. No carbapenemase producer has yet been isolated from a nonhuman sample in Guadeloupe ( 21 23 ), but this should be monitored in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic, metaphylactic and prophylactic use of antibiotics in veterinary medicine is considered to be the main cause for the selection of resistant bacteria in cattle and pigs, which are identified as a major ESBL reservoir [ 13 ]. However, ESBLs are also detected in Enterobacteriaceae isolated from hosts that do not consume antibiotics, i.e., wild fauna [ 14 , 15 , 16 , 17 , 18 ]. Wild birds are the most frequent ESBL carriers among wildlife species and have been proposed as another potential reservoir that can significantly contribute to the diffusion of resistant strains via migration and/or living in close proximity to both humans and other animals [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the wide use of antimicrobials in human and veterinary medicine is one of the risk factors in the selection of antimicrobial-resistant bacteria, reducing the usage of antimicrobial agents is an important approach for preventing the spread of antimicrobial resistance [ 10 , 14 ]. Environments contaminated with human and animal wastes have become reservoirs of antimicrobial-resistant bacteria or resistance genes, and wild animals play a certain role in the spread of antimicrobial resistance [ 2 , 7 , 9 ]. Therefore, the surveillance of antimicrobial-resistant bacteria in wild animals is also important in terms of the One Health approach [ 18 ].…”
mentioning
confidence: 99%